JENIS DAN MAKNA TERJEMAHAN (DITINJAU DARI KELEBIHAN DAN KEKURANGANNYA) - Masduki Masduki (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2011)
Translation as a process of transferring messages involves two distinct languages, source language and target language. Translation also involves different conditions of socio-culture since texts in translation are in place of socio-culture context related to source language and target language. In this process of translating, translator relies on two things, meaning to be translated accurately and types of translation suited to the purposes of translation. Further, this article highlights the definition of translation types, advantages and disadvantages, and meanings of translation.